Óleos essenciais de Lippia origanoides Kunth. e Eremanthus erythropappus (DC.) MacLeish: quantificação do ergosterol sobre os fungos Aspergillus carbonarius, Aspergillus flavus e Aspergillus ochraceus, atividade antiocratoxigênica e antiaflatoxigênica - Brandão, Rafaela Magalhães (2017)
The use of natural products constitutes a possible alternative for the preservation of food quality and the production of new drugs in relation to traditional treatments, because most synthetic products present toxicity and resistance. Currently, the biolo gical potential presented by the constituents of the essential oils has been studied. In this work, the objective was to characterize the chemical constituents of the essential oils from the leaves of Lippia origanoides Kunth and from the core of the Eremanthus erythropappus (DC.) MacLeish wood to evaluate the fungicidal, ochatoxigenic, and aflatoxigenic activities and to identify and quantify ergosterol in the toxigenic fungi tested with the oils. The extraction of the essential oil was accomplished by the hydrodistillation method, using the modified Clevenger apparatus, and the oil was analyzed by CG-MS and CG-DIC. The evaluation of the inhibitory effect of the essential oils, the interference of the oils in the mycelial growth and the inhibition of the er gosterol synthesis were tested on Aspergillus carbonarius (CCDCA 10507), Aspergillus flavus (CCDCA 10508) and Aspergillus ochraceus (CCDCA 10506) species. The anti-ochratoxigenic activity of the essential oils was evaluated through the inhibition of OTA biosynthesis by A. carbonarius and A. ochraceus fungi. The anti-aflatoxigenic activity of the essential oils was evaluated by inhibiting the biosynthesis of AFB1 and AFB2 in culture medium containing different concentrations of each essential oil. The major compounds found in the essential oil of Lippia origanoides Kunth. were carvacrol, ρ-cimene, γ-terpinene and trans-β-caryophyllene. The only compound found in the oil from Eremanthus erythropappus (DC.) MacLeish was α-bisabolol. The antifungal activity of the essential oils was observed for all fungi tested. The essential oils of the species used presented a dose-dependent relationship in the inhibition of mycelial growth, inhibition of ochratoxin A and aflatoxin B1 and B2, and ergosterol synthesis. Antiochratoxigenic and anti-aflatoxigenic activities against fungi were observed. A decrease in the biosynthesis of OTA, AFB1 and AFB2 was observed at all concentrations of the oils tested. A reduction in mycelial growth, as well as ergosterol content, was observed, which demostrated the effect of the essential oils on the plasma membrane of the fungus. The results are promising for drugs because they act on ergosterol biosynthesis.